Effects of Mosaic Land Use on Dynamically Downscaled WRF Simulations of the Contiguous United States. Issue 16 (23rd August 2019) - Mallard, Megan S.; Spero, Tanya L.
Abstract: The representation of land use (LU) in meteorological modeling strongly influences the simulation of fluxes of heat, moisture, and momentum; affecting the accuracy of 2‐m temperature and precipitation. Here the Weather Research and Forecasting (WRF) model is used with the Noah land surface model to compare a mosaic approach, which accounts for subgrid scale variability of LU types, to the default option, which only considers the dominant category in each grid cell. Three‐year historical dynamically downscaled WRF simulations are generated using a 12‐km domain over the contiguous United States to assess the sensitivities to using mosaic LU and to changes to parameters associated with LU and soil categories. Compared to dominant LU, mosaic LU features decreased coverage of forest and agricultural types and increased low‐density urban LU throughout much of the eastern and central U.S. However, highly urbanized areas show the opposite trend, as mosaic LU represents partial greenspace within areas that are exclusively urban within dominant LU. Mosaic LU results in widespread increases in sensible heat fluxes and 2‐m temperatures, with reductions in latent heat flux, 2‐m mixing ratio, and monthly precipitation across the central and eastern U.S. These changes exacerbate an existing warm bias found with dominant LU but reduce overestimations of precipitation. Highly urbanized areas in the eastern U.S. tend to have cooler, more realistic temperatures with mosaic LU relative to dominant LU. A pair of runs with updated surface parameters corroborates these results. Overall, differences between the simulations are largely attributable to their representations of urban LU. Key Points: WRF's Noah LSM is used in a dynamical downscaling application to compare the effects of mosaic land use against using the dominant category Within the United States, mosaic increases urban area and reduces forest and cultivated land, leading to warmer temperatures and less precipitation Within large cities, the opposite trend occurs, as greenspace within cities increases and 2‐m temperatures are reduced